VD_FINDINFO AP / 2011 / 2 vom 25. September 2009 - VD Tribunal cantonal (2009)
CONTRAT D'ENTREPRISE, PRIX FERME, AVIS DES DÉFAUTS, DÉFAUT DE LA CHOSE, VICE DE CONSTRUCTION | 363 CO, 367 CO, 368 al. 2 CO